JAVANESE GRADED READING BOOKS FOR ELEMENTARY SCHOOL STUDENTS - Supartinah Supartinah; Sekar Purbarini Kawuryan; Woro Sri Hastuti (Universitas Negeri Makassar, 2020)
This research was intended to develop graded readers (graded reading books) in the Javanese language for elementary school students. To develop the products, this work usedthe R&D model by Borg and Gall, in which the main procedure was composed of product analysis, product development, expert validation, trials, and product revision. The subjects of this research were the elementary school students and the teachers of Bantul Regency, Sleman Regency, the City of Yogyakarta; experts in the Javanese language;experts in teaching and learning; and experts inteaching and learning media. The sample respondents were obtained through purposive sampling and the data were collected through questionnaires, observations, and interviews. The data were analyzed qualitatively and quantitatively. The products were validated by experts in learning contents, experts in teaching and learning, and experts in teaching and learning media. The result shows that they rated the products very good. The results of questionnaires distributed amongthe teachers and students show that these products carry positive impact on student learning.It can be concluded that the graded reading books are highly recommended for learning activitiesin elementary schools that offer Javanese.